Innovators, firms, and markets : the organizational logic of intellectual property - Barnett, Jonathan M. (New York, NY : Oxford University Press, 2020)
Conventional wisdom holds that robust enforcement of intellectual property (IP) right suppress competition and innovation by shielding incumbents against the entry threats posed by smaller innovators. That assumption has driven mostly successful efforts to weaken US patent protections for over a decade. This text challenges that assumption. In 'Innovators, Firms, and Markets', Jonathan M. Barnett confronts the reigning policy consensus by analyzing the relationship between IP rights, firm organization, and market structure.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 4, 2020).
Keywords: Intellectual property; Patent laws and legislation -- United States -- History